2007
DOI: 10.1002/jmri.21111
|View full text |Cite
|
Sign up to set email alerts
|

MRI identification of the rostral‐caudal pattern of pathology within the corpus callosum in the cuprizone mouse model

Abstract: Purpose: To characterize and compare histological and MRI-based changes within the corpus callosum (CC) in the cuprizone mouse model of multiple sclerosis (MS). Materials and Methods:A total of 12 C57/BL6 mice were fed cuprizone from eight weeks of age for four weeks. One cohort of six cuprizone and two control mice were scanned with a T2-weighted (T2W) sequence. The other cohort of six cuprizone and four control mice were scanned using a dualecho sequence for T2-mapping and a diffusion-weighted sequence with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
92
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 33 publications
19
92
4
Order By: Relevance
“…Our data indicate that up-regulation of the chemokine CXCL12 is essential for the differentiation of CXCR4-expressing OPCs into mature oligodendrocytes within the demyelinated CC in vivo. We show that the pattern of CXCL12 expression mirrors rostralcaudal patterns of pathology previously observed during CPZmediated demyelination (21,22). Thus, highest levels of CXCL12 were expressed by activated astrocytes within caudal sections, which exhibit the most extensive demyelination and glial cell activation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our data indicate that up-regulation of the chemokine CXCL12 is essential for the differentiation of CXCR4-expressing OPCs into mature oligodendrocytes within the demyelinated CC in vivo. We show that the pattern of CXCL12 expression mirrors rostralcaudal patterns of pathology previously observed during CPZmediated demyelination (21,22). Thus, highest levels of CXCL12 were expressed by activated astrocytes within caudal sections, which exhibit the most extensive demyelination and glial cell activation.…”
Section: Discussionsupporting
confidence: 76%
“…Cessation of CPZ after 6 wk is followed by OPC differentiation and remyelination, whereas continued ingestion leads to OPC apoptosis and chronic demyelination. Prior studies have demonstrated that demyelination and glial injury occurs most prominently in the caudal region of the CC and that continued ingestion of CPZ leads to extension of injury to OPCs and decreased remyelination even after cessation of toxin (21,22). Thus, this model provides an opportunity to examine signals associated with both successful and failed remyelination.…”
mentioning
confidence: 99%
“…Another potential limitation is the lack of histological evidence to corroborate our MRI findings. Although previous studies have validated MRI measures against histology,72, 73, 74 this study would have been strengthened by complementary histological studies. Lastly, while it is unlikely that the rats reached sexual maturity during the course of this study, future investigations may want to examine the effects of estrous cycle on postinjury recovery.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the supra-hippocampal portion of the CC which at more caudal position was described, while in the study of Silvestroff et al (2012) the brain sections were analyzed at a more rostral level. In fact, it has been shown that cuprizone induced demyelination produces a dramatic rostrocaudal gradient of white matter demyelination, with the caudal CC more injured than rostral area (Wu et al, 2008;Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%